Childhood, Science Fiction, and Pedagogy Children Ex Machina - Kupferman, David W.; Gibbons, Andrew; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book invites readers to both reassess and reconceptualize definitions of childhood and pedagogy by imagining the possibilities - past, present, and future - provided by the aesthetic turn to science fiction. It explores constructions of children, childhood, and pedagogy through the multiple lenses of science fiction as a method of inquiry, and discusses what counts as science fiction and why science fiction counts. The book examines the notion of relationships in a variety of genres and stories; probes affect in the convergence of childhood and science fiction; and focuses on questions of pedagogy and the ways that science fiction can reflect the status quo of schooling theory, practice, and policy as well as offer alternative educative possibilities. Additionally, the volume explores connections between children and childhood studies, pedagogy and posthumanism. The various contributors use science fiction as the frame of reference through which conceptual links between inquiry and narrative, grounded in theories of media studies, can be developed.
Introduction: Why childhood ex machina? -- Part I Relationship -- Franken-education, or when science runs amok -- The monstrous voice: M.R. Carey's The Girl with All the Gifts -- Toy Gory, or the Ontology of Chucky: Childhood and killer dolls -- Part II Affect -- Through the Black Mirror: Innocence, abuse, and justice in "Shut Up and Dance" -- Your Android Ain't Funky (or Robots Can't Find the Good Foot): Race, Power, and Children in Otherworldy Imaginations -- Tension, Sensation, and Pedagogy: Depictions of Childhood's Struggle in Saga and Paper Girls -- Part III Pedagogy -- A Utopian Mirror: Reflections from the future of childhood and education in Aldous Huxley's Brave New World and Island -- Filling the mind: Cortical knowlege uploads, didactic downloads, and the problem of learning in the future -- Heretic Gnosis: Education, children, and the problem of knowing otherwise -- "Life is a Game, So Fight for Survival": The neoliberal logic of educationalcolonialism within the Battle Royale Franchise -- Part IV Conclusion -- Children and Pedagogy Between Science and Fiction.
Keywords: Education -- Philosophy; Sociology; Social groups; Culture -- Study and teaching; Sociology -- Methodology; Education -- Research; Educational Philosophy; Sociology of Family, Youth and Aging; Cultural Studies; Sociological Methods; Philosophy of Education; Research Methods in Education